(untitled) (Philology, 2026)
The purpose of this study is to analyze the literary devices – especially similes – used in the poetry of Magtymguly Pyragy, the classical poet and sage of the East. Similes taken from the poet’s lines are revealed through distinct group classifications. The poet’s works are a valuable treasure for studying the national heritage of the Turkmen people, as they contain the richness of the Turkmen language and literature. His poems use the style of Eastern poetry and are also distinguished by their closeness to the folk language, which is rich in literary devices such as similes, comparisons, metaphors, and others. One can learn how to use literary devices skillfully by looking at Magtymguly’s poems – as a master of eloquence who uses words in different ways for stylistic purposes. Similes are among the most commonly used and effective literary devices, as they enhance comparisons without sacrificing clarity, playing an important role in the poet’s work. Similes are the focus of this article. The poet used similes as both direct and figurative comparisons by associating one object with another from an entirely different class of things or historical context. This allows the reader to grasp the author’s ideas and the moral of the poem more clearly. In this article, the frequent use of similes is observed, and their formation is analyzed. These similes are grouped into various categories and subcategories in Magtymguly’s poetry.